Improving The Ability of Teachers To Arrange Knowledge Aspect Assessment Instruments Through Collaborative Academic Supervision - Sumadi, Sumadi; Ismanto, Bambang (Universitas Negeri Malang, 2021)
This study aims to improve the ability of teachers to compile instruments for assessing aspects of knowledge through collaborative supervision in Kenteng 01 Elementary School, Bandungan District. This type of research is a school action research with a qualitative descriptive approach. The research subjects consisted of school principals and 6 teachers at Kenteng 01 Elementary School. Data collection techniques were done through observation, interviews, and documentation studies. Data analysis techniques used are data collection, data analysis, data reduction, data presentation, and conclusions. This research was conducted in two cycles through planning, implementation, observation, and reflection. The results showed that after academic supervision in cycle 1, the average score was 78.9 C (enough). In cycle 2 the average score was 90.4 in the good category (B).